A one pot diazo installation-photochemical oxidation (blue LED-O2)/ amidation of aryl/heteroaryl acetates with cyclic 2°-amines: An eco-friendly synthesis of aromatic α-ketoamides. (22nd October 2022) - Maiti, Debajit; Prabakar, Tejas; Ghosh, Poushaly; Sen, Subhabrata
Abstract: Aromatic-α-ketoamides are an interesting class of molecules. They have myriad biological properties and are also frequently used as building blocks for the synthesis of heterocyclic scaffolds. Herein we have reported an eco-friendly synthesis of aromatic-α-ketoamides. It is a one pot synthesis beginning from alkyl aryl/heteroaryl acetates 7a - k with various cyclic secondary amines 8a - c in molecular oxygen as the oxidant via diazo installation-oxidation-amidation in ethyl acetate as solvent with a 5–6 W Micro Photochemical Reactor with blue LED lights (435–445 nm) to the target compounds. The reaction could also be performed under air with no oxidant but that facilitated major formation of the undesired NH-inserted products. Under oxygen atmosphere the formation of such by-products was minimized to 10–20%. Various aromatic-α-ketoamides 10a - x were synthesized in moderate to good yields. Control experiments provided rational for the mechanism of transformation. This protocol could be scaled up in gram scale. Graphical abstract: Image 1